Pengelolaan Keuangan Desa Ditinjau Dari Undang-Undang Desa Menuju Masyarakat Yang Mandiri - Etty Susmilawaty Manik (Officium Notarium, 2021)
According to Article 16 paragraph (1) of Law Number 2 of 2014, a notary must be precautious in carrying out their function. However, in the Yogyakarta High Court Decision No. 34/Pdt/2017/PT YYK, a notary has made the deed of Sale and Purchase of Land in full with a clause of right to repurchase and is based on debts. The formulation of the problem in this study is, how is the notary's responsibility in the making of a notarial deed containing a false cause? This research is a normative research with a case, legislation, and conceptual approaches and analyzed in a qualitative way. The results of this study conclude that the Notary is civilly responsible for the making of a notarial deed (AIJB No. 01) containing a false cause because it was proven to be inaccurate, causing losses as referred to in Article 1365 of the Civil Code. Whereas the national land law does not recognize the sale and purchase of land with a clause on the right to buy back and must be viewed as a debt agreement.Keywords: Deed; false causes; notary; responsibilityAbstrakMenurut Pasal 16 ayat (1) Undang-Undang Nomor 2 Tahun 2014, seorang notaris harus seksama dalam menjalankan jabatannya. Namun dalam Putusan Pengadilan Tinggi Yogyakarta No. 34/Pdt/2017/PT YYK, seorang notaris telah membuat akta Ikatan Jual Beli tanah lunas dengan klausul hak membeli kembali dan dilatarbelakangi utang piutang. Rumusan masalah dalam penelitian ini yakni, bagaimana petanggungjawaban notaris dalam pembuatan akta notariil dengan kausa palsu? Penelitian ini adalah penelitian normatif dengan pendekatan kasus, perundang-undangan, serta konseptual serta dianalisa dengan cara kualitatif. Hasil penelitian ini menyimpulkan, Notaris bertanggungjawab secara perdata atas pembuatan akta notariil (AIJB No 01) berkausa palsu sebab terbukti tidak cermat sehingga menyebabkan kerugian seperti dimaksud dalam Pasal 1365 KUHPerdata. Padahal hukum pertanahan nasional tidak mengenal jual beli tanah dengan klausul hak membeli kembali dan harus dipandang sebagai perjanjian utang piutang.Kata Kunci: Akta; kausa palsu; notaris; tanggungjawab